The arabic version of the fat phobia scale—short form: reliability and structural validity - Hadeel Ghazzawi; Ahmad Alenezi; Sally Souraya; Omar Alhaj; Khaled Trabelsi; Adam Amawi; Mai Helmy; Zahra Saif; Beatrice “Bean” E. Robinson; Haitham Jahrami (Eating and Weight Disorders)
Abstract Background Weight bias, often known as fat phobia or weight stigma, refers to unfavorable attitudes and stereotypes that are associated with, and applied to, larger bodies. Fat phobia can include an unreasonable and abnormal dread of being overweight or being associated with obese people. Currently, there is no validated tool available to measure fat phobia in Arabic. Measuring fat phobia in Arabic-speaking populations is crucial, because cultural attitudes toward body weight can be quite negative and discriminatory; these negative attitudes can negatively impact mental health. The current study aimed to adapt, translate, and assess the structural validity of the Fat Phobia Scale—Short Form (F-Scale 14) in Arabic. Methods The gold standard approach to translation was used. Forward translation involved translation from the English language to the Arabic language by independent translators. Subsequently, a back-translation review was performed on the translated Arabic version for comparison with the original language. A cross-sectional study was conducted online that included 1246 participants from 22 Arabic countries, of whom 74% were female, 66% single, 83% university graduates, with a mean age of 35 ± 6 years. Results The F-Scale 14 demonstrated good reliability in the Arabic language, with a Cronbach’s α of 0.82 (95% CI 0.80–0.83), comparable to the original scale. The test–retest reliability of the scale was 0.92 (95% CI 0.90–0.94). According to the fit indices, the F-Scale 14 demonstrated a satisfactory level of structural validity in Arab cultures. Fit indices are statistical measures used in confirmatory factor analysis (CFA) to assess how well a proposed model fits the observed data. The scale showed a small improvement in factorial structure after the removal of some items. The two items removed were self-indulgent versus self-sacrificing and disliking food versus likes food. The correlation between F-Scale 14 and the figure rating scale was r = 0.76 (p < 0.001), suggesting adequate convergent validity. Conclusions The F-Scale 14 is a crucial indicator of attitudes and opinions concerning obese or overweight individuals. Based on increased internal consistency reliability and the problematic cultural relevance of two items, we recommend adopting a 12-item version of the scale for better cultural relevance in Arabic populations. It is anticipated that the Arabic F-Scale-12 will be highly useful for research and clinical purposes. Future research should test and adapt the Fat Phobia Scale for diverse Arabic populations to ensure its cultural relevance. Exploring its application in clinical settings will enhance our understanding of weight stigma and inform targeted interventions that promote body positivity. By addressing these areas, we can develop effective strategies to foster healthier attitudes toward body image in Arabic communities. Level V: Evidence obtained from a cross-sectional descriptive study.